THE EFFECT OF STRESS DURING ONLINE LEARNING ON MEDICAL STUDENT’S LEARNING ACHIEVEMENT IN COVID-19 PANDEMIC - Putu Nandika Tungga Yudanti Mahardani; Sri Darmayani; Dyah Kanya Wati; Maria Elisabeth Sylvinna Wasi Elannor; Ketut Wulan Ari Kartika Ardhaputri; Andreliano Yosua Rompis (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Medical students are a population that is considered vulnerable to experience stress during the COVID-19 pandemic, especially with the heavy learning load and changes in the learning system that were initially carried out face-to-face. Currently, there are limited data regarding the stress of studying online in medical students and their effect on learning achievement. This study aimed to determine the stress effect of studying online in medical students on their academic achievement.Methods: This study was an analytic observational study with a cross-sectional approach. 112 samples were obtained from students of Bachelor of Medicine and Medical Doctor in one of the universities in Bali with the instruments that were distributed via Google Form. Primary data collection was carried out using the Medical Student Stressor Questionnaire (MSSQ) questionnaire, while secondary data collection was obtained from the average score of three-block exams done online during the COVID-19 pandemic.Results: The stress level of medical students in online learning was dominated by high stress (55.4%) with the majority cause due to Academic Related Stressor (ARS). There is a significant relationship (p = 0.021) between the incidence of stress and learning achievement in students (-0.217, 95% CI -0.39 to -0.03). The learning system preference that was chosen by the students is dominated by a 50% online learning system and 50% offline as much as 27.7%.Conclusion: The results indicated that there is a high level of stress among medical students. There is a correlation between stress events and medical student’s achievement during online learning.